Determinants of Insurance Enrollment - Asfaw, Gudeta Kebede (Utan Kayu Publishing, 2022)
Ownership of health insurance policy is a mechanism for protecting an individual family’s financial security. It is also a means for a risk-aversion strategy for the cost of medical care, loss of productivity time during the illness, and in a more serious case death. This study examines the factors that influence the ownership of insurance policies at an individual level using a binary logistic regression model. The data used in this study was taken from the Health and Retirement Study (HRS), the fifth wave in 2002 with 3206 respondents of the survey, whereby thirty-nine percent of the respondents happened to have an insurance policy scheme. The outcome of this model indicated that retirement status, household income, years of schooling, and marital status variables were all found to have a statistically (at 95% confidence level) associated with ownership of insurance policy. Contrastingly, the other covariates, namely: age at the time of the survey, race, and gender of the respondents had insignificantly relationship with the ownership of insurance policy.